STRUKTUR MUSIK IRINGAN TARI JEPIN TEMPURUNG DESA TEKELAK KECAMATAN PINOH UTARA KABUPATEN MELAWI - Yunisa Is Yuniarti, Tria; Ismunandar, Ismunandar; Muni ir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe background of this research was to describe the description musical structure of Jepin Tempurung dance. The purpose of this research was to describe the musical structure of Jepin Tempurung dance in Tekelak Village, North Pinoh District, Melawi Regency, West Kalimanantan. Theories used in this research were structure, music, music of dance accompaniment, musicology, ethnomusicology, ethnomusicology approach, rhythm pattern, and musical form. The method used in this research was explorative descriptive method. This form of this research was qualitative. The approach of this research was the musical approach. The data of this research were interview result, observation result, and documentation result. Data collection techniques of this research were observation, interview, and documentary study. Data collection tools of this research were researcher as main instrument, interview guidelines, observation guidelines, and documentation tools. The validity checkout of this research data were the extension of observation and triangulation technique. The data analysis technique of this research were the analysis during data collection and analysis after data collection.Keywords: the musical structure,  musical accompaniment, Jepin Tempurung dance.